FORECASTING BUDGET REQUIREMENT FOR INDONESIAN ARMS MODERNISATION WITH INTERNATIONAL COST ESCALATION (ICE) - Maharani, Curie; Noor, Reyhan; Pratama, Sandy J; Wicaksono, Ganesh A. (Global: Jurnal Politik Internasional, 2026)
In 2021, the question "How much is enough" emerged in national debate following the plan of the then Indonesian Defence Minister, Prabowo Subianto, to allocate 1.7 quadrillion Rupiah for military modernisation from 2020 to 2045. This article follows up on this debate by recommending a budget forecasting model for the weapons acquisition requirements of the Indonesian National Defence Forces (TNI) during the period 2025 to 2044. The model is built by considering International Cost Escalation (ICE), which is the increase in the unit cost of successive generations of similar weapons, causing a steady increase in the price of weapons systems each year. Four main variables are integrated into the forecasting framework: the need for modernisation of 10 selected weapon systems categorised by two technology sources (Western and Eastern), macroeconomic growth trends, the defence burden to GDP and investment (modernisation spending) as a percentage of total defence spending, and the value of the selected ICE. This study concludes the following: (1) there are three possible scenarios for the modernisation of Indonesia's weapons systems based on technology sources from Western countries, Eastern countries, and a combination of Western and Eastern countries (diversification); (2) current macroeconomic conditions and defence burdens are not sufficient to support full-scale modernisation using Western technology alone.